2009
DOI: 10.1007/s00259-008-1037-1
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear imaging in cardiac amyloidosis

Abstract: Amyloidosis is a disease characterized by depositions of amyloid in organs and tissues. It can be localized (in just one organ) or systemic. Cardiac amyloidosis is a debilitating disease and can lead to arrhythmias, deterioration of heart function and even sudden death. We reviewed PubMed/Medline, without time constraints, on the different nuclear imaging modalities that are used to visualize myocardial amyloid involvement. Several SPECT tracers have been used for this purpose. The results with these tracers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 70 publications
0
38
0
5
Order By: Relevance
“…It provides images of amyloid load that can be used to compliment routine diagnosis by histochemical analysis of tissue biopsies, aid in prognostication, and document response to therapy (24,25). Although 123 I-SAP scintigraphy is the most common imaging technique for the detection of amyloid in the peripheral organs, other methods using 99m Tc-aprotinin and 99m Tc-3,3-diphosphon-1,2-propanodicarboxylic acid for imaging cardiac amyloid and ATTR, respectively, are also available (26)(27)(28)(29)(30). These methods are rarely used, however, because of the nonspecific nature of the interaction.…”
mentioning
confidence: 99%
“…It provides images of amyloid load that can be used to compliment routine diagnosis by histochemical analysis of tissue biopsies, aid in prognostication, and document response to therapy (24,25). Although 123 I-SAP scintigraphy is the most common imaging technique for the detection of amyloid in the peripheral organs, other methods using 99m Tc-aprotinin and 99m Tc-3,3-diphosphon-1,2-propanodicarboxylic acid for imaging cardiac amyloid and ATTR, respectively, are also available (26)(27)(28)(29)(30). These methods are rarely used, however, because of the nonspecific nature of the interaction.…”
mentioning
confidence: 99%
“…14 Tc-DPD, widely used in Europe but unavailable in the United States, has had similarly excellent reported efficacy, showing ≈100% discrimination between amyloid type in small studies, whereas larger studies showed greater overlap. [15][16][17] That being said, Tc-DPD uptake is considered strongly suggestive of TTR.…”
Section: Ruberg and Miller Nuclear Tracers For Ttr Cardiac Amyloidosimentioning
confidence: 99%
“…However its use in the heart is hampered by blood pool uptake [71] and it is available only in a few highly specialized centers. 99m-Tc-aprotinin may be fairly specific for cardiac amyloidosis but experience with this tecnique is limited [72].…”
Section: Radioisotope Imagingmentioning
confidence: 99%